Circulating Fibroblast Growth Factor 21 and Total Testosterone in Type 2 Diabetes Mellitus Men With Coronary Heart Disease - Mei, Yufeng; Lyu, Yongnan; Zhao, Zhiming; Li, Yan (Frontiers in Endocrinology, 2022)
Background: Fibroblast growth factor 21 increased in population with type 2 diabetes mellitus (T2DM), and serum total testosterone often decreased in men with T2DM. This study aimed to investigate the relationship between the prevalence of coronary artery disease (CAD) and circulating FGF21 concentrations and serum testosterone in T2DM men. Methods: 490 men with T2DM from January 2021 to December 2021 were recruited from the Renmin Hospital of Wuhan University, and they were divided into CAD group (n=248) and control group (n=242). FGF21 were determined based on ELISA principle and serum total testosterone was measured in a liquid chromatography mass spectrometer LC/MS-8050 (Shimadzu, Japan). Logistic and restricted cubic spline analyses were performed to examine the association between the prevalence of CAD and circulating FGF21 concentrations and serum testosterone in T2DM men. The receiver operating curve (ROC) analysis was used to explore the predictive performance. Results: Circulating FGF21 levels were higher in T2DM men with CAD compared with those without CAD [214.63 (121.82, 348.64) pg/ml vs 166.55 (94.81,254.48) pg/ml, p<0.001], while serum total testosterone was lower [3.08±0.07 ng/ml vs 3.76±0.09 ng/ml, p<0.001]. The fully adjusted odds ratio (OR) and 95% confidence intervals (95%CI) was 2.956(1.409,6.201) for those in quartile 4 of FGF21 versus quartile 1 and the fully adjusted OR (95%CI) was 0.346(0.174,0.686) for those in quartile 4 of testosterone versus quartile 1. The receiver operating curve (ROC) analysis showed that the area under the curve (AUC) of combination of FGF21 and testosterone for predicting the occurrence of CAD in men with T2DM was 0.702 (95% CI: 0.667-0.741). Conclusion: Circulating FGF21 levels were positively associated with CAD in men with T2DM, whereas serum total testosterone levels showed an inverse correlation with CAD in diabetic men.